Inverse analysis of surrounding rock parameters of loess tunnels and numerical simulation analysis of stress-seepage coupling under water migration - Jun-jie Xuan; Ming Li; Yao-hui Du; Jia-qi Lin; Yue Gao; Yun-cheng Mao; Kun Zhang (Scientific Reports)
Abstract In this study, the Tuanjie Tunnel project on the Tongwei-Dingxi Expressway is utilized to investigate the stress-seepage coupling in loess tunnels. Field monitoring, laboratory experiments, and numerical simulations were employed to establish a coupled numerical model of the stress-seepage field for the shallow-buried sections of these tunnels. The seepage-stress interactions in loess tunnels were analyzed, revealing variations in pore water pressure around the tunnel and the deformation behavior of surrounding rock during construction, with particular attention to the effects of water migration.The results indicate that when the groundwater level is 10 m from the tunnel crown, the pressure of pore water at various measurement points follows an order of tunnel invert > arch springing > arch waist > arch haunch > tunnel crown. Within the pipe roof reinforcement zone, pore water pressure increases with distance from the tunnel perimeter, while above the zone, it decreases with distance. When considering water migration, the excavation of the upper bench significantly impacts the vertical effective stress at each point, the excavation of the middle bench impacts the arch wall and the haunch, and the excavation of the lower bench impacts the springing of the arch.Based on these insights, addressing the challenges encountered during the construction of water-rich loess tunnels, the implementation of pipe roof reinforcement measures for surrounding rock has played a positive role in enhancing the stability of loess tunnels during construction.